Sensory and Chemical Characteristic of Dry Bakpia with Formulations of Wheat Flour and Kepok Banana Flour (Musa acuminata balbisiana Colla) - Oktabriyana, Tiara; Nawansih, Otik; Satyajaya, Wisnu; Rizal, Samsul; Nurainy, Fibra (Jurnal Agroindustri Berkelanjutan, 2025)
Bakpia is a traditional round-shaped pastry filled with mung beans, wrapped in dough, and baked. This study aimed to determine the formulation of wheat flour and kepok banana flour that produced dry bakpia with the best sensory and chemical characteristics. A Completely Randomized Design (CRD) with a single factor was used, involving six formulations of wheat flour and kepok banana flour: P1 (100:0), P2 (90:10), P3 (80:20), P4 (70:30), P5 (60:40), and P6 (50:50), each replicated four times. Sensory evaluations (color, texture, taste, and aroma) and chemical analyses (moisture, ash, protein, fat, carbohydrate, and crude fiber contents) were conducted. The results showed that the P2 formulation (90% wheat flour : 10% kepok banana flour) produced bakpia with the best sensory characteristics, including a slightly dark white color, moderately layered crumbly texture, and a distinctive banana flavor and aroma. The chemical characteristics of the P2 formulation included 11.40% moisture, 2.6% ash, 14.85% protein, 13.02% fat, 58.13% carbohydrate, and 3.13% crude fiber. Keywords: dry bakpia, kepok banana flour, sensory evaluation, chemical analysis